Sistem Pakar E-Rapor untuk Prediksi Minat Bakat dan Roadmap Pendidikan Siswa dalam Pemilihan Sekolah - Nurohmah, Siti; Wibisono, Iwan Setiawan (Jurnal Algoritma, 2025)
Choosing a school and university that does not match students' interests and talents often leads to regret later on. According to Irene Guntur, an Educational Psychologist from Integrity Development Flexibility (IDF), 87% of students in Indonesia feel they are in the wrong major. In addition, the Minister of Education, Culture, Research, and Technology (Mendikbudristek) Nadiem Makarim stated that 80% of students in Indonesia do not work in accordance with the major they took. This is due to students' lack of understanding of their interests and talents, as well as the influence of friends, family, or people closest to them in the decision-making process. This study aims to develop an integrated e-report system that is able to identify students' interests and talents based on academic data from elementary, junior high, to high school levels. This system provides recommendations for relevant schools and universities, and functions as a promotional platform for educational institutions through profile information, vision, mission, and blogs. The development of the system follows the Waterfall method which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. . Student academic data in grades 6, 9, and 12 is the basis for system analysis. The results of the study show that the system is able to increase the accuracy of recommendations by up to 95%, while providing an effective promotional medium for schools and universities. This system is expected to help students make better educational decisions, minimize external influences, and encourage educational institutions to improve their competitiveness and service quality. These findings contribute to the development of innovative, effective and predictive technology-based educational information systems.